THE INFLUENCE OF CHINESE CULTURAL VALUES ON BALINESE TRADITIONAL PAINTING - Karja, I Wayan (UPT Pusat Penerbitan LP2MPP ISI Bali, 2024)
This research examines the influence of Chinese cultural values on the development of Balinese painting, focusing on how cultural interactions have enriched its artistic identity. Using qualitative methods with a historical approach and visual analysis, the study identifies Chinese cultural elements such as Yin-Yang philosophy, cosmology, motifs like Nekara Pejeng, Chinese coins, dragons, and decorative techniques integrated into Balinese art. The findings reveal that these influences are most evident in the styles of Kamasan painting, where forms, colors, and decorative motifs reflect a process of acculturation. Balinese artists have successfully incorporated these Chinese elements into their works while preserving their cultural identity. This research highlights the importance of cultural exchange as a driving force in the evolution of Balinese painting, offering both academic and practical contributions to the understanding of how cross-cultural interactions can enhance artistic traditions.